Outcome of radial scar/complex sclerosing lesion associated with epithelial proliferations with atypia diagnosed on breast core biopsy: results from a multicentric UK-based study. Issue 12 (26th July 2019) - Rakha, Emad; Beca, Francisco; D'Andrea, Mariangela; Abbas, Areeg; Petrou-Nunn, William; Shaaban, Abeer M; Kandiyil, Aneeshya; Smith, Samantha; Menon, Sindhu; Elsheikh, Somaia; ElSayed, Maysa E; Lee, Andrew HS; et al.
Abstract : Aims: The clinical significance of radial scar (RS)/complex sclerosing lesion (CSL) with high-risk lesions (epithelial atypia) diagnosed on needle core biopsy is not well defined. We aimed at assessing the upgrade rate to ductal carcinoma in situ (DCIS) and invasive carcinoma on the surgical excision specimen in a large cohort with RS/CSL associated with atypia. Methods: 157 women with a needle core biopsy diagnosis of a RS/CSL with atypia and follow-up histology were studied. Histological findings, including different forms of the atypical lesions and final histological outcome in the excision specimens, were retrieved and analysed, and the upgrade rates for malignancy and for invasive carcinoma were calculated. Results: 69.43% of the cases were associated with atypical ductal hyperplasia (ADH) or atypia not otherwise classifiable, whereas lobular neoplasia was seen in 21.66%. On final histology, 39 cases were malignant (overall upgrade rate of 24.84%); 12 were invasive and 27 had DCIS. The upgrade differed according to the type of atypia and was highest for ADH (35%). When associated with lobular neoplasia, the upgrade rate was 11.76%. The upgrade rate's variability was also considerably lower when considering the upgrade to invasive carcinoma alone for any associated lesion. Conclusions: The upgrade rate for ADH diagnosed on needle core biopsy with RS is similar to that of ADH without RS and therefore should be managed similarly. RS associated with lobular neoplasia is less frequently associated with malignant outcome. Most lesions exhibiting some degree of atypia showed a similar upgrade rate to invasive carcinoma. Management of RS should be based on the concurrent atypical lesion.